2014
DOI: 10.1159/000357472
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability Analysis with Inertial Measurement Units in Alzheimer's Disease

Abstract: Background: The cause of frequent falls in patients with Alzheimer's disease (AD) is still not well understood. Nevertheless, balance control and sensory organization are known to be critical for moving safely and adapting to the environment. Methods: We evaluated postural stability in 20 AD patients (11 fallers and 9 nonfallers) and 16 healthy controls with an inertial measurement unit (triaxial accelerometers and gyroscopes) attached to the center of mass (COM) in different balance conditions (Romberg on fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
1
36
1
1
Order By: Relevance
“…Table 1 summarizes participant characteristics and settings for the studies included in this review. As shown in Table 1, sample size varied widely among articles, from 20 to 358 participants, with 2 studies [31,32] including data from agematched control participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 summarizes participant characteristics and settings for the studies included in this review. As shown in Table 1, sample size varied widely among articles, from 20 to 358 participants, with 2 studies [31,32] including data from agematched control participants.…”
Section: Resultsmentioning
confidence: 99%
“…Study design varied across articles (see Table 2): 3 studies were cross-sectional with one baseline assessment [31,32,38], 9 studies involved a gait/balance assessment at baseline (also cross-sectional) with a follow-up for up to 2, 3, 4, 5, 12, or 24 months to record occurrence of fall incidents [2,12,13,24,26,32,[34][35][36][37], and 2 studies included repeated gait and balance data collection throughout the follow-up period [23,39]. One study [29] collected gait and balance measures at baseline and captured a measure of tortuosity continuously over a 1-year period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the goal of postural control is to maintain the center of mass (COM) within the limits of stability, direct measurement of COM may provide better insights into the mechanisms of balance control [11]. Numerous studies have reported using acceleration-based and gyroscope-based sway metrics for assessing balance deficits in older adults at risk of falling [12], in patients with Parkinson disease [13], MS [14, 15], and Alzheimer disease [16]. However, conventional inertial sensor(s) often still need to be synced with a host computer through additional hardware, and the sensor needs to be secured using straps or other means.…”
Section: Introductionmentioning
confidence: 99%